A preliminary study on topical cetirizine in the therapeutic management of androgenetic alopecia. (17th February 2018) - Rossi, A.; Campo, D.; Fortuna, M. C.; Garelli, V.; Pranteda, G.; De Vita, G.; Sorriso-Valvo, L.; Di Nunno, D.; Carlesimo, M.
Abstract: Background: Androgenetic alopecia (AGA) is a common form of scalp hair loss that affects up to 50% of males between 18 and 40 years old. Several molecules are commonly used for the treatment of AGA, acting on different steps of its pathogenesis (Minoxidil, Finasteride, Serenoa repens) and show some side effects. In literature, on the basis of hypertrichosis observed in patients treated with analogues of prostaglandin PGF2a, it was supposed that prostaglandins would have an important role in the hair growth: PGE and PGF2a play a positive role, while PGD2 a negative one. Objective: We carried out a pilot study to evaluate the efficacy of topical cetirizine versus placebo in patients with AGA. Patients and methods: A sample of 85 patients was recruited, of which 67 were used to assess the effectiveness of the treatment with topical cetirizine, while 18 were control patients. Results: We found that the main effect of cetirizine was an increase in total hair density, terminal hair density and diameter variation from T0 to T1, while the vellus hair density shows an evident decrease. The use of a molecule as cetirizine, with no notable side effects, makes possible a good compliance by patients. Conclusion: Our results have shown that topical cetirizine 1% is responsible for a significant improvement of the initial framework of AGA.